Disfunción familiar y bajo rendimiento académico en estudiantes de bachillerato de la Unidad Educativa Fiscomisional La Dolorosa de Loja - Flores España, Ximena del Cisne (2020)
Families can be facilitators or an impediment to the academic performance of the children, in such a way that the inconsistencies, the lack of tranquility and stability in them are factors that place the student in a climate of affective insecurity that is not conducive to a good adaptation school. This research aims to establish the relationship between family dysfunction and low academic performance in 285 high school students of the Loja Fisor Commission Educational Unit, this study is analytical and correlational, with a cross-sectional quantitative approach, in the which we apply an instrument to detect family dysfunction (APGAR) and record the grades of the academic performance act. The chi-square test was used to perform the statistical analysis, with a 95% confidence level, and a p value of <0.05. From the results obtained in the investigation, we determined that family dysfunction does not present a relationship of statistical association with low academic performance, where the chi-square value, with a degree of freedom is 2.49 with a p value of 0.120 and a association coefficient of phi v of creamer of 0.092. Conclusion: dysfunctional families do not constitute a determining risk factor in poor academic performance, since it is a multifactorial variable. Key words: family dysfunction, academia, functionality, Apgar.